2022
DOI: 10.3390/su15010549
|View full text |Cite
|
Sign up to set email alerts
|

The Enabling Effect of Intellectual Property Strategy on Total Factor Productivity of Enterprises: Evidence from China’s Intellectual Property Model Cities

Abstract: Does intellectual property (IP) strategy improve the total factor productivity of enterprises (TFP)? This paper uses 21,930 enterprise-year observations of China’s A-share listed enterprises from 2010–2020, adopts a multi-period difference-in-differences model, and constructs a quasi-natural experiment on the impacts of intellectual property model cities (IPMC) on TFP. The findings are as follows: (1) IPMC significantly improves TFP. (2) It has lag effects and long-term effects. (3) The promotion effect is str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Secondly, our research is related to the literature on how IPR protection influences enterprise GTI. Previous literature has investigated the relationship between IPR protection and total factor productivity (TFP) from the perspective of the government-business relationship and innovative expenditure [28]. In our study, we advance further by exploring the mechanism of foreign investment entry and R&D investment, as well as the moderating role of human capital and financing capacity.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Secondly, our research is related to the literature on how IPR protection influences enterprise GTI. Previous literature has investigated the relationship between IPR protection and total factor productivity (TFP) from the perspective of the government-business relationship and innovative expenditure [28]. In our study, we advance further by exploring the mechanism of foreign investment entry and R&D investment, as well as the moderating role of human capital and financing capacity.…”
Section: Introductionmentioning
confidence: 92%
“…Roh et al note that IPR protection positively impacts GTI through open innovation using Korean manufacturing data from 2014 to 2016 [27]. Furthermore, The relationship between IPR protection and total factor productivity (TFP) is studied as well [28], indicating a positive relationship between them.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some literature has examined the impact of IPDC on firm-level innovation. Zhu and Sun [45] found that the IPDC program promotes technological innovation and thus increases total factor productivity in firms. Fang, Lerner [8] found that the IPDC program promoted innovation and was particularly effective for private companies.…”
Section: The Impact Of Intellectual Property Protection On Innovationmentioning
confidence: 99%
“…On the one hand, one of the focuses of the IPDC program is to facilitate intellectual property pledge financing services so that companies can more easily obtain financing support [47]. Enterprises can use their intellectual property as collateral to obtain financing, which can reduce the cost and risk of financing for enterprises and improve their financing ability [45]. IPDC program can also provide intellectual property valuation and trading services, enabling…”
Section: External Financing Constraint Relief Mechanism Successful In...mentioning
confidence: 99%